Low-grade, systemic inflammation in adolescents: association with early-life factors, gender, and lifestyle. - Pirkola, J; Vääräsmäki, M; Ala-Korpela, M; Bloigu, A; Canoy, D; Hartikainen, A; Leinonen, M; Miettola, S; Paldanius, M; Tammelin, T; Järvelin, MR; Pouta, A (2010)
Low-grade, systemic inflammation is related to increased risk of cardiovascular disease in adults. The proinflammatory state tracks from adolescence to adulthood. Identifying correlates of inflammation in adolescents could provide opportunities to prevent cardiovascular disease in adulthood. However, population-based data on correlates of inflammation in adolescence are limited. Therefore, the authors studied the associations of early-life factors, gender, and lifestyle with inflammation (measured by high-sensitivity C-reactive protein and leukocyte count) at age 16 years (2001-2002) in the prospective, population-based Northern Finland Birth Cohort 1986 Study (n = 5,240). In females, being born small for gestational age and current use of oral contraceptives were associated with the proinflammatory state. The association of birth size with inflammation was not observed in males. In logistic regression analyses, oral contraceptive use (odds ratio (OR) = 2.83), abdominal obesity (OR = 5.17), and smoking (OR = 2.72) were associated with elevation of both inflammation markers in females; abdominal obesity (OR = 5.72) and smoking (OR = 2.02) were associated in males. Thus, females appear more susceptible to the adverse effects of being born small for gestational age than males. Given the widespread use of oral contraceptives and the potential pathophysiologic consequences of the proinflammatory state, the association of oral contraceptive use with inflammation in adolescence may have public health implications.